Impacto ambiental de bandejas Biodegradables a base de Almidón de Camote (ipomoea batatas) y Fibra de Caña de Azúcar (saccharum officinarum), utilizando huella ecológica emergética - Escobedo Honores, Renato (2017)
The objective of the present work was to determine environmental impact of biodegradable trays based on sweet potato starch (Ipomoea batatas) and sugar cane fiber (Saccharum officinarum). In order to determine environmental impact of the biodegradable trays, ecological footprint method was used, biocapacity was calculated according to renewable resources present in the study (sun, wind, rain and biomass), in turn the ecological footprint was calculated taking categories of consumption such as loss of soil, materials in agriculture, services, electricity consumption, etc. In both cases, biocapacity and emergent ecological footprint were expressed in global hectares. As a result of this process, a positive ecological balance of 4054,18 gha was obtained, it indicates that biodegradable trays have a positive environmental impact.